Exegesis on the Integral-Interaction: a Conceptual Foundation in Nursing - Phoebe Lynn B Calungsod; Joel Rey Ugsang Acob (Faculty of Nursing, Universitas Jember, 2020)
Caring nurses fulfill the relation among other health professionals in the pursuit of quality and valuable attention towards people across the walks of life. Hence, an adequate interaction among stakeholders must transpire as central in the nursing practice. This manuscript clarify concepts on integral interactive based on reviews of published literature and to further explain the components of integral interaction as nursing concept. The study utilized pragmatic utility as an approach in analyzing reviewed literature concepts. A prism is also employed during systematic literature review. Keywords used such as caring, interaction, integral and the like to extract significant articles as unit of analysis. The nursing profession is not possible without nurse-client interaction as this serves as the backbone to which practice has relied on. This concept analysis is focused on the idea that an integral interaction must occur in every nurse-client interaction. On the event of clarifying what is integral to nursing where a more comprehensive view is elaborated that is very useful in the delivery of nursing care not only towards the client but in collaboration with other health care team in the attainment of client’s well-being. Integral-interaction explain that nurse-patient relationship only exists when the three components are experienced simultaneously. It is also recommended to further the investigation by applying the conceptual model to practice in clinical or community settings therefore strengthening the claim of studied concepts.